Review essay: central banking through the centuries - Ivo Maes (National Bank of Belgium, 2018)
Anniversaries are occasions for remembrance and reflections on one's history. Many central banks take the occasion of an anniversary to publish books on their history. In this essay we discuss five recent books on the history of central banking and monetary policy. In these volumes, the Great Financial Crisis and the way which it obliged central banks to reinvent themselves occupies an important place. Although this was certainly not the first time in the history of central banking, the magnitude of the modern episode is remarkable. As comes clearly to the fore in these volumes, there is now, also in the historiography of central banking, much more attention to the (shifting) balance between price stability and financial stability. The history of central banking is more perceived as one of an institution whose predominant concern varied between "normal" times and "extraordinary" times. So, central banks will have to remain vigilant, as one should expect financial crises to return. Moreover, the new world of central banking, with a greater responsibility of central banks for financial stability, will make life more complicated for central banks. It may have also consequences for central bank independence, as the modalities of the two mandates, price and financial stability, are not the same. Another aspect which comes to the fore in these volumes is the relationship between central banking and state formation. Historically, central banks have been embedded in processes of nation-building. By extending their network of branches across the country, or by being at a center of a system of liquidity provision, ultimately tied to the national currency, they played a key role in the shaping of "national economies".
Keywords: E42; E58; G28; N10; 330; central banking; financial stability; price stability; Great Financial Crisis